A cross‐case comparison of the trauma and orthopaedic hospital experiences of adults with intellectual disabilities using interpretative phenomenological analysis - Mary Drozd; Darren Chadwick; Rebecca Jester (Wiley, 2021)
Abstract Aim To present the cross‐case comparison component of a qualitative study exploring and describing the experiences of adults with an intellectual disability who have received trauma and orthopaedic hospital care for musculoskeletal conditions or injuries in the United Kingdom. Design A qualitative, exploratory study was conducted using 1:1 semi‐structured interviews to describe the lived experiences of trauma and orthopaedic hospital care from the perspectives of people with intellectual disabilities and a carer of a person with profound and multiple intellectual disabilities. The data were analysed using interpretative phenomenological analysis. The Standards for Reporting Qualitative Research guidelines were applied. Results There were common and interconnected experiences across the five participants: communication challenges; lack of person‐centred care; issues related to pain management; lack of confidence in hospital care; the valuable support and expertise of carers; and incompetence of hospital staff and isolation and loneliness.